Analisis Strategi Pemasaran dengan Menggunakan Metode SWOT pada Rumah Makan Griyo Semar Mesem - Mia Nardila Galih Wilujeng; Faizal Satria Desitama; Siswahyudianto; Nadia Rosmalita Sari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The restaurants in Tulungagung Regency has increased every year. Because of this increase, competition in the restaurant business become fierce. Businessman must have the right marketing strategy to obtain the desired target market. The right marketing strategy can be obtained from several analytical tools in marketing strategy. One of these analytical tools is to use SWOT analysis as used in this research. This research aims to understand the internal and external factors that influence the Griyo Semar Mesem Restaurant, as well as formulating marketing strategies that can be implemented by the restaurant. The research method used is descriptive qualitative, which describes in detail the influence of internal and external factors, as well as determining the marketing strategy for Griyo Semar Mesem Restaurant. This research was carried out through depth interviews and observation. The results of marketing strategy analysis using the SWOT method show placement in quadrant I, which supports the implementation of aggressive strategies. The aggressive strategy includes market penetration, product development, vertical integration, and diversification